Soul survivor the reincarnation of a World War II fighter pilot - Leininger, Bruce; Leininger, Andrea; Gross, Ken, 1938- (New York Grand Central Pub., 2009)
"The dramatic story of how one couple finds that their young son is the reincarnation of a World War II pilot"--Provided by the publisher
95546
Keywords: Leininger, James -- 1998-; Leininger, Bruce; Leininger, Andrea; Huston, James M. -- d. 1945.; Reincarnation; Fighter pilots -- United States; World War, -- 1939-1945; Lafayette (La.)